SEMANGAT KERJA GURU SMP NEGERI DI KECAMATAN GUGUAK KABUPATEN LIMA PULUH KOTA - Ratna Melia (Universitas Negeri Padang, 2013)
The research aimed to see teachers morale, the population is 173 teacher people and samples is 65 teachers. This type of research is descriptive. In this study, researchers conducted data collection by distributing questionnaires. This research is done in the first secondary school at sub district guguak, Lima Puluh Kota district Payakumbuh. After the study concluded that the morale of the teacher in that school is hight. Kata kunci: Semangat kerja